Change in the notion of madness. The Hospital of the Innocent of Valencia - Alfonso Fernández Vázquez (Universidad de Alicante, 2015)
The objective of the present article is to reveal the history of the Hospital of the Innocent of Valencia and its impact on the conception of madness. This study will describe which cares received the patients in this institution. The method employed has been the research and reading of numerous bibliographic sources. The conclusions of this study resaltan the importance of Gilabert Jofré like promoter of the foundation of the hospital. His speech produced a change in the deal of the patient of mental health. The Hospital of Valencia supposed a sanitary revolution in psychiatric cares, including new treatments like the occupational therapy.